2021
DOI: 10.52054/fvvo.13.1.009
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate injection for interstitial pregnancy: Hysteroscopic conservative mini-invasive approach.

Abstract: Background: Interstitial localisation of ectopic pregnancy is associated with high rates of maternal morbidity and mortality. Considering the rarity of interstitial pregnancy, the optimal treatment regimen remains unclear. We propose the management of interstitial pregnancy with local methotrexate injection using a combined hysteroscopic and ultrasonographic approach. Technique: Hysteroscopy was performed under local anaesthesia in the operating room, using a 2.9-mm Hopkins II Forward-Oblique Telescope 30° end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…In a case series of laparoscopic-assisted hysteroscopic removal of IP, Niu et al concluded that if the mass distent the uterine cornua with a tunnel connecting the mass and the cornua, hysteroscopic resection is likely to be successful 13 . In a series of five patients, Casadio et al successfully treated IP with local hysteroscopic MTX injection 14 . Hysteroscopic assisted local MTX injection could minimize adverse systemic effects of MTX 14,15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case series of laparoscopic-assisted hysteroscopic removal of IP, Niu et al concluded that if the mass distent the uterine cornua with a tunnel connecting the mass and the cornua, hysteroscopic resection is likely to be successful 13 . In a series of five patients, Casadio et al successfully treated IP with local hysteroscopic MTX injection 14 . Hysteroscopic assisted local MTX injection could minimize adverse systemic effects of MTX 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…In a series of five patients, Casadio et al successfully treated IP with local hysteroscopic MTX injection 14 . Hysteroscopic assisted local MTX injection could minimize adverse systemic effects of MTX 14,15 . This modality, combined with our report of two cases, seems promising for the management of IP.…”
Section: Discussionmentioning
confidence: 99%
“…In replacing traditional laparotomy, early diagnosis of interstitial pregnancy before rupture makes various minimally invasive methods of treatment possible [3]. These medical management approaches include expectant management [3]; laparoscopic surgery [9] with reversible occlusion of uterine arteries and cornuostomy for advanced cases [18]; hysteroscopic management [6,10,14]; medical cytotoxic management [11] with mifepristone [12]; and endovascular therapy [8] with cytotoxic infusional chemotherapy [4].…”
Section: Discussionmentioning
confidence: 99%
“…If rupture occurs in the interstitial portion of the uterus, which includes abundant blood supply from a complex pelvic vascular network composed of the uterine artery and anastomosing ovarian artery, definitive management involves life-saving intervention either by laparotomy or, more recently, laparoscopy [3]. However, for the management of hemodynamically stable cases without rupture, a wide range of surgical and non-surgical procedures are available [3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…MTX and mifepristone act synergistically and promote lysis of the trophoblast cells [ 19 ]. Alternatives to medical therapy are mentioned in the literature, namely, hysteroscopy combined with medical treatment [ 15 , 20 ], laparoscopic cornual resection [ 21 ], laparoscopic cornuostomy [ 22 , 23 ], and in the more severe cases laparotomic hysterectomy [ 24 ]. Minimally invasive surgery is indicated for elective procedures.…”
Section: Discussionmentioning
confidence: 99%